Eksplorasi Kreativitas Visual Anak: Studi Kasus Pembuatan Karya Seni Kolase Bahan Daur Ulang - Pratiwi, Ika Ari; Hartono, Hartono; Rokhman, Fathur; Wagiran, Wagiran (PGSD Universitas Muria Kudus, 2025)
Elementary school students’ visual creativity has often not been fully explored due to limited media and conventional approaches to art education. This study aims to explore how creating collage artworks using recycled materials can serve as a means of stimulating the visual creativity of third-grade students at SD 1 Gulang Kudus. The main issue examined is how the process and outcomes of children’s visual creativity emerge through collage activities using recycled bottle caps. The study employed a qualitative approach with a descriptive case study method, involving 30 students from SD 1 Gulang Kudus. Data were collected through participatory observation, documentation of students’ artworks, and interviews with teachers and students. Data analysis in this case study research uses data reduction, data presentation and conclusions.The results showed that the use of recycled bottle caps stimulated exploration of unique forms, colors, and compositions, enhanced students’ confidence in self-expression, and strengthened environmental awareness. Students demonstrated improvement in originality, elaboration, and flexibility in visual thinking. The study implies that integrating eco-friendly materials into art learning is an effective strategy for fostering creativity while instilling values of sustainability from an early age. Teachers are expected to be more innovative in selecting media and providing students with opportunities for free exploration.